La invisibilitat com a matèria política: Vermell de Cadmi de Margarida Aritzeta i Los invisibles de José María Merino - Gregori, Alfons (Studia Romanica Posnaniensia, 2018)
Invisibility is the main motif of two non-mimetic novels belonging to the Catalan and Spanish literature respectively: Vermell de Cadmi [Cadmium Red] (1984) by Margarida Aritzeta, and Los invisibles [The Invisible] (2000) by José María Merino. The aim of the present article is to compare both novels by analysing how the dialectical process between body, fantasticality, and social conflict works in them, taking into account their historic and literary contexts, possible interpretations of the unusual events from an ideological point of view, and the strategies used for achieving the fantastic effect in both of them.